2021
DOI: 10.1002/ncp.10625
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Implementing Exclusive Human Milk Diet to Extremely Low‐Birth‐Weight Infants in a Level III Neonatal Intensive Care Unit

Abstract: Problem: Extremely low‐birth‐weight (ELBW) infants require fortification of human milk (HM) to prevent growth failure. Bovine milk–based fortifiers (BOV‐f) may be associated with feeding intolerance and necrotizing enterocolitis. Evidence suggests that an exclusive HM diet (EHMD) using HM‐based fortifier (HM‐f) may improve these outcomes. Intervention: EHMD was introduced as a quality improvement project to improve feeding tolerance in ELBW infants. Method: Implementation included establishing EHMD feeding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Our data provides further support of trends identi ed in other studies, [38][39][40]43,44 including that growth in weight, length, and head circumference on an EHMD diet is comparable to that on a formula or bovineforti ed diet. This contradicts other studies about growth outcomes related to breastmilk versus formula or bovine forti cation in this population 35,36 but may be attributable to forti cation in the post-EHMD group taking place an average of almost 8 days earlier than in the pre-EHMD group. There were no differences between groups in other parameters that may potentially be related to nutrition when evaluated at the time of transition off EHMD, including serum sodium and serum alkaline phosphatase, and there was even an improvement in the post-EHMD group in hematocrit and serum albumin.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Our data provides further support of trends identi ed in other studies, [38][39][40]43,44 including that growth in weight, length, and head circumference on an EHMD diet is comparable to that on a formula or bovineforti ed diet. This contradicts other studies about growth outcomes related to breastmilk versus formula or bovine forti cation in this population 35,36 but may be attributable to forti cation in the post-EHMD group taking place an average of almost 8 days earlier than in the pre-EHMD group. There were no differences between groups in other parameters that may potentially be related to nutrition when evaluated at the time of transition off EHMD, including serum sodium and serum alkaline phosphatase, and there was even an improvement in the post-EHMD group in hematocrit and serum albumin.…”
Section: Discussioncontrasting
confidence: 88%
“…Bushati C et al showed improved feeding tolerance but worse growth with EHMD compared to bovine-based forti cation of human milk. 35 Eibensteiner F et al published data from multiple centers demonstrating no difference in rates of NEC but worse growth velocity for babies receiving the EHMD diet compared to those on human milk forti ed with bovine-based forti er. 36 However, other studies suggest than an exclusive human milk diet (EHMD: MOM or DHM forti ed with human milk-based forti er) improves feeding tolerance and NEC without detrimental effects on growth compared to human milk forti ed with bovine-based forti ers and/or preterm formula.…”
Section: Introductionmentioning
confidence: 99%
“…This is usually achieved with parenteral solutions of essential amino acids or enteral feeding with human milk supplemented with bovine or human milk‐based fortifiers 2 . High‐protein nutrition can be challenging in when ELBW neonates have phenylketonuria (PKU), due to the lack of a phenylalanine‐free amino acid solution for parenteral nutrition 3 . PKU is an autosomal recessive metabolic disease of phenylalanine metabolism that is caused by deficient activity of phenylalanine hydroxylase (PAH), an enzyme that converts phenylalanine into tyrosine.…”
Section: Introductionmentioning
confidence: 99%
“…10 The combination of HM-derived fortifiers with either DM or MOM, excluding any products cow's milk-containing products, has been labeled as exclusive HM diet. 11 Fat in HM is an important energy source for enterally fed growing term and premature infants. 12 Infants may have developmental limitations in utilizing milk-borne fats in the first few weeks after birth.…”
mentioning
confidence: 99%